5‐Hydroxymethylfurfural Production from Glucose, Fructose, Cellulose, or Cellulose–based Waste Material by Using a Calcium Phosphate Catalyst and Water as a Green Solvent. Issue 3 (30th January 2017) - Mimura, Naoki; Sato, Osamu; Shirai, Masayuki; Yamaguchi, Aritomo
Abstract: We successfully prepared 5‐hydroxymethylfurfural from glucose, fructose, cellulose, natural wood, waste paper, and cotton clothing by using a calcium phosphate catalyst and water as a green solvent. The combination of basic and acidic sites on the surface of the calcium phosphate catalyst accelerated the multistep reaction pathway from the reactants to 5‐hydroxymethylfurfural. Ball‐milling pretreatment of the reactant markedly increased the yield of 5‐hydroxymethylfurfural obtained from cellulose, natural wood, waste paper, and cotton clothing. Abstract : We identified a calcium phosphate catalyst that had high catalytic activity for the conversion of glucose or ball‐milled cellulose to HMF with water as a green solvent. The catalytic system was also effective for the conversion of natural wood, and cellulose‐based waste materials (100 % cotton clothing and paper) to HMF.